Pengukuran Kinerja Pembangunan Sektor Pendidikan Dasar di Indonesia - Ronny Dicky Wijaya Sinaga (Populasi, 2011)
Education is an important issue, both regionally and globally. This research describes the measurement of the development performance in basic education in Indonesia (by the year 2000 and 2007) considering the compulsory of 9 years education (Wajardiknas Policy) which launched in 1994, but lost its pamour during the reform and early of autonomy era. The launching of Inpres. No. 5/2006 has strengthen the policy and sincronized it to the MGDs related to education which should be accomplished in 2015. This research is a secondary data analysis usingdata from IFLS 2000 and 2007. Some of the results of this research is that there was an increasing in the educational expenses, but the number of students who should be paid for it have decreasing significantly. The government should pay more attention on the APM in Junior High which still lower than the national target. Students coming from poor families also should have more attention from the government in finishing their education, especially in relation with the educational expenses.Pendidikan menjadi isu penting, baik secara nasional maupun global. Penelitian ini mendeskripsikan hasil pengukuran kinerja pembangunan pendidikan dasar di Indonesia (tahun 2000 dan 2007) mengingat kebijakan Wajardiknas 9 Tahun yang dicanangkan tahun 1994 kehilangan pamornya saat reformasi dan masa awal otonomi daerah. Terbitlah Inpres No. 5 Tahun 2006 untuk menguatkan kembali kebijakan itu dan kembali mengarahkan tujuan MDGs bidang pendidikan di tahun 2015. Penelitian ini merupakan analisis data sekunder Sakerti 2000 dan 2007 yang diolah secara cross sectional. Hasil penelitian ini, antara lain, adalah peningkatan biaya pendidikan secara drastis, tetapi secara kuantitatif jumlah siswa yang dipungut biaya pendidikan menurun secara signifikan. APM untuk SMP juga masih jauh dari target nasional sehingga dibutuhkan perhatian ekstra dari pemerintah. Siswa miskin juga perlu mendapat perhatian untuk menuntaskan pendidikannya, terutama dari segi pembiayaannya.